Rapid and cost-effective process based on insect larvae for scale-up production of SARS-COV-2 spike protein for serological COVID-19 testing - Smith, Ignacio (2021)
Serology testing for COVID-19 is important in evaluating active immune response against SARS-CoV-2, studying the antibody kinetics, and monitoring reinfections with genetic variants and new virus strains, in particular, the duration of antibodies in virus-exposed individuals and vaccine-mediated immunity. In this study, recombinant S protein of SARS-CoV-2 was expressed in Rachiplusia nu, an important agronomic plague. One gram of insect larvae produces an amount of S protein sufficient for 150 determinations in the ELISA method herein developed. We established a rapid production process for SARS-CoV-2 S protein that showed immunoreactivity for anti-SARS-CoV-2 antibodies and was used as a single antigen for developing the ELISA method with high sensitivity (96.2%) and specificity (98.8%). Our findings provide an efficient and cost-effective platform for large-scale S protein production, and the scale-up is linear, thus avoiding the use of complex equipment like bioreactors.